Unraveling the nexus of drought stress and rice physiology: mechanisms, mitigation, and sustainable cultivation - Wen-fei Hu; Ye-bo Qin; Jun-jiang Lin; Ting-ting Chen; San-feng Li; Yu-tiao Chen; Jie Xiong; Guan-fu Fu (Plant Stress)
In the face of global warming, drought is becoming an increasingly severe issue and has emerged as a crucial factor affecting agricultural production. Investigating the effects of drought stress on the growth, development, and physiological traits of rice, elucidating the underlying response mechanisms of rice to drought stress, and exploring agronomic practices to reduce yield losses under such stress are essential for boosting rice yields in arid conditions and safeguarding global food security. This review comprehensively synthesizes the latest research progress on the changes in the growth, development, and physiological characteristics of rice under drought stress, as well as the regulatory mechanisms of drought tolerance. It delves deeply into the stress responses and energy metabolism patterns of rice induced by drought stress. Moreover, it systematically summarizes the establishment of drought tolerance evaluation systems and the screening methods for drought-tolerant rice varieties. At the same time, it outlines practical agronomic measures and management strategies for combating drought stress, aiming to provide a scientific basis for rice cultivation in drought-affected regions.